Effects of dietary Clostridium autoethanogenum protein on the growth, disease resistance, intestinal digestion, immunity and microbiota structure of Litopenaeus vannamei reared at different water salinities - Chen, Jian; Wang, Hongming; Yuan, Hang; Hu, Naijie; Zou, Fangqi; Li, Chongyang; Shi, Lili; Tan, Beiping; Zhang, Shuang (Frontiers in Immunology, 2022)
The shortage of fishmeal (FM) resources limits the healthy development of aquaculture. Developing new protein sources to replace FM in aquatic feeds is an effective measure to alleviate this situation. However, the application effect of new protein sources is greatly affected by water salinity, which is an important parameter of aquaculture. In this study, the growth, disease resistance, and intestinal digestion, immunity, and microbiota structure of Litopenaeus vannamei (initial weight: 0.38±0.01 g) fed on Clostridium autoethanogenum protein (CAP) or not at three different water salinities (15 ‰, 30 ‰, and 45 ‰) were compared, aiming to explore the effects of dietary CAP on shrimp when suffering different salinity stresses. The results showed that the growth performance, feed utilization, and survival rate (SR) after pathogen challenge of L. vannamei could be significantly improved by dietary CAP when compared with the control at the same salinity and they were also significantly affected by salinity changes when L. vannamei was fed on the same protein source. With the increase in salinity, obvious upregulation was observed in the activities and gene expression of digestive enzymes both in L. vannamei fed on FM and CAP, with significantly higher levels in L. vannamei fed on CAP than in those fed on FM at the same salinity. Meanwhile, the expression levels of immune genes in the CAP group were significantly higher than those in the FM group at different salinities. The intestinal microbiota analysis showed that CAP could increase the relative abundance of beneficial bacteria and decrease the relative abundance of harmful bacteria in the intestine of L. vannamei at the phylum, family, and genus levels, and it was more affected by salinity changes when compared with FM. Besides, the changes in salinity and protein sources led to different changes in the intestinal microflora function of L. vannamei. In sum, this study indicated that CAP could improve the growth, disease resistance, digestive capacity, and intestinal microflora of L. vannamei with a much more intense immune response and enhance its ability to cope with salinity stress.